The study of antimicrobial and antifungal activity of Nʹ-ylidene-2(3-(adamantan-1-yl)-1H-1,2,4-triazole-5-yl)thioacetohydrazides - V. M. Odyntsova (Zaporozhye State Medical University, 2015)
Aim. The modern arsenal of antimicrobial drugs is characterized by high toxicity, moreover their widespread and uncontrolled use leads to the resistant strains' selection. It creates favorable basis for the synthesis of new compounds with pronounced pharmacological activity. Methods and results. The primary screening of antimicrobial and antifungal activity of synthesized Nʹ-ylidene-2(3-(adamantan-1-yl)-1H-1,2,4-triazole-5-yl)thioacetohydrazides has been conducted by twofold serial dilutions method in liquid nutrient media in order to identify among the synthesized compounds those ones which have high antimicrobial and antifungal activities. Due to the results of the study the compounds that exceed the standard, according to the activity of comparison, have been identified. Some relationship's patterns as «structure-activity» have been established. Conclusion. It indicates the need to expand the search spectrum of promising compounds towards the museum and clinical strains of infectious diseases' pathogens.